Botanical origin, physicochemical characterization, and antioxidant activity of bee pollen samples from the northeast of Portugal - Pascoal, Ananias (2022)
Bee pollen is a beehive product that has increased the attention of both researchers and consumers. The main goal of the present study was to evaluate 69 heterofloral dried bee pollen samples harvested in two regions of the northeast of Portugal (Mogadouro and Vimioso). For such, the botanical origin of the samples and several physicochemical parameters (moisture, pH, water activity, reducing sugar, proteins, lipids, ash, fibers, carbohydrates, energy, total phenolic, and flavonoids) were evaluated and the antioxidant potential was studied. The average percentage of pollen grains from Erica spp. and Cytisus spp. was higher (p<0.05) in samples from Mogadouro, while Cistus spp., Castanea spp., and Echium spp. were more abundant in Vimioso samples. The pollen harvested in Vimioso presented higher values on proximate parameters as compared to other samples:moisture (4.61 ± 0.84%), lipids (4.94 ± 0.94%), ash (3.28 ± 0.93%), fiber (3.55 ± 1.11%), and carbohydrates (66.60 ± 3.52%).On the other hand, higher values were obtained on Mogadouro samples regarding water activity (0.41 ± 0.11), protein (26.09 ± 2.86%), total phenols (26.71 ± 6.19, expressed as mg of Gallic acid equivalents GAE/g), and antioxidant activity (assessed by b-carotene bleaching [3.35 ± 1.17mg/mL] or the free radical scavenging assay [2.98 ± 0.63mg/mL]). All bee pollen samples had a great botanical similarity, yet the dominant pollen types were different between the two regions allowing the classification of the samples according to the geographical origin.